Online Fingerprint Authentication Scheme over Outsourced Data - Tilak B,; Vaishnavi N. , (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
With the rifeness of mobile plans and the growth of biometric technology, biometric credentials, which can realize separate verification trusts on individual life or social physiognomies, has involved widely substantial interest. Though, confidentiality subjects of biometric data bring out increasing worries due to the extremely compassion of biometric data. Aiming at this test, in this project, we current a novel privacy-preserving online fingerprint verification arrangement, named e-Finga, over encoded subcontracted data. In the proposed e-Finga scheme, the user’s fingerprint registered in trust authority can be subcontracted to dissimilar servers with user’s approval, and safe, precise and well-organized verification service can be provided without the leakage of fingerprint information. Exactly, an better homomorphic encryption skill for secure Euclidean distance calculation to realize an efficient online fingerprint matching algorithm over encrypted Finger Code data in the subcontracting scenarios. Through detailed safety analysis, we show that e-Finga can fight various security intimidations. In addition, we implement e-Finga over a workstation with a real fingerprint database, and extensive imitation results prove that the proposed e-Finga scheme can serve well-organized and precise online fingerprint verification.
Keywords: Biometric Authentication; Privacy-Preserving Verification; Online Fingerprint Matching; Outsourced Data; Homomorphic Encryption; Secure Euclidean Distance Calculation; Fingerprint Data Protection; Cloud Security; e-Finga Scheme; Data Confidentiality